Joint roles of parenting and nutritional status for child development: Evidence from rural Cambodia. Issue 5 (28th June 2019) - Berkes, Jan; Raikes, Abbie; Bouguen, Adrien; Filmer, Deon
Abstract: Substantial work has demonstrated that early nutrition and home environments, including the degree to which children receive cognitive stimulation and emotional support from parents, play a profound role in influencing early childhood development. Yet, less work has documented the joint influences of parenting and nutritional status on child development among children in the preschool years living in low‐income countries. Using panel data from 2016 to 2017 on the parenting, nutritional status, and early developmental outcomes (executive function, language, early numeracy, and socioemotional problems) of 6, 508 Cambodian children ages 3–5 years, our findings demonstrate that inequities in early development associated with family wealth are evident at age 3 and increase among children ages 4 and 5 years. Using hierarchical regression analysis, a significant share of these inequalities is explained by differences in parenting and early nutritional status, measured by stunting. Better‐educated parents engage in more stimulating and supportive parenting practices. However, the positive association between parenting and language and early numeracy outcomes is 35–54% stronger for non‐stunted children, and parental activities explain only about 8–14% of the cognitive gap between the lowest and highest wealth quintiles. The results highlight the need for additional research outlining interactions between environmental factors that link family wealth and child development. Abstract : Inequities in early development associated with family wealth are evident at age 3 and increase among children ages 4 and 5 years. A significant share of these inequalities is explained by differences in parenting and early nutritional status. The positive association between parenting and language and early numeracy outcomes is 35–54% stronger for non‐stunted children.